Isolation and characterization of exopolysaccharide‐producing strains of Lactobacillus bulgaricus from curd. Issue 4 (3rd March 2019) - Ali, Khubaib; Mehmood, Muhammad Huzaifa; Iqbal, Muhammad Ahmad; Masud, Tariq; Qazalbash, Mudassir; Saleem, Shahzad; Ahmed, Sheraz; Tariq, Muhammad Rizwan; Safdar, Waseem; Nasir, Muhammad Adnan; Saeed, Muhammad Tariq; Muhammad, Abid; et al.
Abstract: Curd is the most widespread traditional fermented milk product used by a large population and is a good source of vitamin B, protein, and calcium. In this study, the isolation of exopolysaccharide (EPS)‐producing strains of Lactobacillus delbrueckii subsp. bulgaricus from curd samples was carried out. Identification of EPS‐producing strains was done by Gram staining, catalase activity, sugar fermentation test, API 50 CHL, and PCR analysis. These EPS‐producing strains were subjected for the estimation of technological properties such as titratable acidity, curdling time, acidification rate, and texture. The strains best in their technological properties were selected for the production of yogurt in combination with EPS‐ or non‐EPS‐producing strains of Streptococcus thermophilus. The EPS concentration range was from 41 to 268 mg/L in the yogurt. The highest value of EPS concentration was detected in S. thermophilus and non‐EPS‐producing Lb. bulgaricus after 14 days of storage. Abstract : Different isolation methods were used to isolate various Lactobacillus bulgaricus samples of curd. Exopolysaccharides enhance the rheological properties of the prepared yogurt.